Predicting the effect of voids on mechanical properties of woven composites - Choudhry, R. S.; Sharif, Tahir; Khan, Kamran Ahmed; Khan, Sohaib Z.; Hassan, Abid; Khan, Muhammad Ali (IOP Publishing, 2018)
An accurate yet easy to use methodology for determining the effective mechanical properties of woven fabric reinforced composites is presented. The approach involves generating a representative unit cell geometry based on randomly selected 2D orthogonal slices from a 3D X-ray micro-tomographic scan. Thereafter, the finite element mesh is generated from this geometry. Analytical and statistical micromechanics equations are then used to calculate effective input material properties for the yarn and resin regions within the FE mesh. These analytical expressions account for the effect of resin volume fraction within the yarn (due to infiltration during curing) as well as the presence of voids within the composite. The unit cell model is then used to evaluate the effective properties of the composite.